On the movement of atmospheric blocking systems and the associated temperature responses - J. van Mourik; J. van Mourik; J. van Mourik; H. de Vries; M. Baatsen (Weather and Climate Dynamics)
The quasi-stationary behaviour of atmospheric blocking is studied using a Lagrangian framework that enables the tracking of blocks in space and time. By combining a blocking index based on geopotential height with a Lagrangian tracking algorithm, we investigate the characteristics of atmospheric blocking events for different zonal velocities with respect to Earth's surface and their impacts on surface temperatures within the retuned EC-Earth3 global climate model. We observe that blocking events can portray a large variety of zonal velocities. Distinct differences are found between the behaviour of eastward-moving blocks and westward-moving blocks, both in size and in spatial distribution. Although the size of blocks is of bigger importance for the temperature anomalies, the zonal velocity has an influence on the strength of the temperature anomalies in winter, due to the slower mechanism of air advection in winter, compared to diabatic heating in summer. In summer, the zonal velocity primarily influences the positioning of temperature anomalies relative to the centre of the blocking system. These findings highlight the complex interactions between size, zonal velocity, and other blocking attributes, as well as their influence on temperature anomalies. Further research is warranted to explore regional differences in blocking behaviour and impact, as well as how atmospheric blocking and associated temperature anomalies may evolve under future climate conditions.